2015
DOI: 10.1080/09540121.2015.1021745
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to highly active antiretroviral therapy impact on clinical and economic outcomes for Medicaid enrollees with human immunodeficiency virus and hepatitis C coinfection

Abstract: We examined the impact of antiretroviral treatment adherence among Hepatitis C co-infected HIV patients on survival and clinical outcomes. We analyzed Medicaid claims data from fourteen southern states from 2005-2007, comparing survival and clinical outcomes and cost of treatment for HIV and hepatitis-C co-infected patients (N=4,115) at different levels of adherence to antiretroviral therapy.More than one in five patients (20.5%) showed less than 50% adherence to antiretroviral treatment, but there were no rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…A study done in South Africa [ 36 ] and Ethiopia [ 23 ] also reported the same findings that adherence is known to contribute to the QoL of PLWHA, as persons with greater ability to adhere to their ART regimens have better QoL. Adherence is found to improve clinical conditions of patients and suppress viral load [ 37 – 39 ] which in turn influence QoL.…”
Section: Discussionmentioning
confidence: 88%
“…A study done in South Africa [ 36 ] and Ethiopia [ 23 ] also reported the same findings that adherence is known to contribute to the QoL of PLWHA, as persons with greater ability to adhere to their ART regimens have better QoL. Adherence is found to improve clinical conditions of patients and suppress viral load [ 37 – 39 ] which in turn influence QoL.…”
Section: Discussionmentioning
confidence: 88%
“…Considering the social stigma associated with depression 27 , it is possible that HIV patients who had a better relationship with their physician were more likely to report their depressive symptoms than those with a poorer relationship. In addition, ART adherence study of HIV and viral hepatitis C (HCV) co-infected individuals also revealed that PDC >95% group had higher proportion of HCV treatment using the 2005–2007 Medicaid claims data 28 . Overall, improved patient-clinician relationships could enhance ART adherence 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Acquired Immune Deficiency Syndrome (AIDS) is an emerging disease and one of the major health problems today, due to its pandemic status and severe characteristics. A reduction of mortality rate associated with the success of antiretroviral therapy (ART) has been observed 1 . However, the disease still has a strong impact on the lives of people living with aids, mainly due to stigma and prejudice, psychiatric disorders such as depression, changes in marital relationships such as abandonment of the partner, and difficulties in keeping and reintegrating into the job market with consequent possible financial problems that may negatively influence ART adherence 2 .…”
Section: Introductionmentioning
confidence: 99%